2015
DOI: 10.53555/nnmce.v2i3.360
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of Mechanical Properties of Fe2O3 Particulate Filled Hybrid Composites

Abstract: The researchers are quite concentrating at the hybrid materials. this is mainly due to their applicable benefits have they offer low density, low cost,etc., an experimental investigation was conducted to study the effect of hematite ore and volume fraction on Tensile Strength, Hardness, Impact Strength of Hybrid composite. General Purpose resin or Orthophthalic resin, E-Glass fiber, and Hematite ore are the constitute of hybrid composite. Specimen was cut from the fabricated laminate according to the ASTM stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…Then increase in the filler content was believed to generate adequate stress transfer and amplification in the reinforcement experienced therefore causing an increase in TS and TM of the composites. These results are in agreement with previous research works by Alam and Choi, 51 Chavan et al 52 and Channapagoudra et al 53 Alam and Choi 51 investigated the reinforcing and magneto mechanical properties of natural-rubber (NR) composites using iron oxide/multilayer graphene (MLG) as hybrid filler. The results showed that magneto-sensitive mechanical properties through the incorporation of iron oxide of about 2.91 vol.% iron oxide were greatly improved, the tensile strength of the composite with the iron oxide/MLG hybrid filler was 160% higher than that of unfilled rubber.…”
Section: Tensile Strength and Tensile Modulussupporting
confidence: 91%
See 3 more Smart Citations
“…Then increase in the filler content was believed to generate adequate stress transfer and amplification in the reinforcement experienced therefore causing an increase in TS and TM of the composites. These results are in agreement with previous research works by Alam and Choi, 51 Chavan et al 52 and Channapagoudra et al 53 Alam and Choi 51 investigated the reinforcing and magneto mechanical properties of natural-rubber (NR) composites using iron oxide/multilayer graphene (MLG) as hybrid filler. The results showed that magneto-sensitive mechanical properties through the incorporation of iron oxide of about 2.91 vol.% iron oxide were greatly improved, the tensile strength of the composite with the iron oxide/MLG hybrid filler was 160% higher than that of unfilled rubber.…”
Section: Tensile Strength and Tensile Modulussupporting
confidence: 91%
“…The rise in the FS and FM also indicated that there was a satisfactory mix of the matrix and filler particles as the filler content increased. 64 This investigation is similar to the investigation reported by Chauhan et al, 68 Channapagoudra et al 53 and Chavan et al 52 Channapagoudra et al 53 studied the effect of hematite filler material on the mechanical properties of glass/epoxy composites prepared via the hand lay-up technique. The tensile flexural impact and hardness behaviour of the resultant composites were investigated.…”
Section: Effect Of Filler Contentsupporting
confidence: 80%
See 2 more Smart Citations
“…Recently, iron oxides such as α-Fe2O3 and magnetite (Fe3O4) have attracted lots of attention in coming up with novel materials. This is due to their interesting electrical and magnetic characteristics, among other characteristics [13,24]. Of all iron oxides, α-Fe2O3 also called ferric oxide (FO) is the most stable.…”
Section: Introductionmentioning
confidence: 99%